Drugs with a negative impact on cognitive functions (part 3): antibacterial agents in patients with chronic kidney disease - Liabeuf, Sophie; Hafez, Gaye; Pešić, Vesna; Spasovski, Goce; Bobot, Mickaël; Mačiulaitis, Romaldas; Bumblyte, Inga Arune; Ferreira, Ana Carina; Farinha, Ana; Malyszko, Jolanta; Pépin, Marion; Massy, Ziad A; et al. (Oxford University Press (OUP), 2024)
The relationship between chronic kidney disease (CKD) and cognitive function has received increased attention in recent years. Antibacterial agents (ABs) represent a critical component of therapy regimens in patients with CKD due to increased susceptibility to infections. Following our reviewing work on the neurocognitive impact of long-term medications in patients with CKD, we propose to focus on AB-induced direct and indirect consequences on cognitive function. Patients with CKD are predisposed to adverse drug reactions (ADRs) due to altered drug pharmacokinetics, glomerular filtration decline, and the potential disruption of the blood-brain barrier. ABs have been identified as a major cause of ADRs in vulnerable patient populations. This review examines the direct neurotoxic effects of AB classes (e.g. beta-lactams, fluoroquinolones, aminoglycosides, and metronidazole) on the central nervous system (CNS) in patients with CKD. We will mainly focus on the acute effects on the CNS associated with AB since they are the most extensively studied effects in CKD patients. Moreover, the review describes the modulation of the gut microbiota by ABs, potentially influencing CNS symptoms. The intricate brain-gut-kidney axis emerges as a pivotal focus, revealing the interplay between microbiota alterations induced by ABs and CNS manifestations in patients with CKD. The prevalence of antibiotic-associated encephalopathy in patients with CKD undergoing intravenous AB therapy supports the use of therapeutic drug monitoring for ABs to reduce the number and seriousness of ADRs in this patient population. In conclusion, elucidating AB-induced cognitive effects in patients with CKD demands a comprehensive understanding and tailored therapeutic strategies that account for altered pharmacokinetics and the brain-gut-kidney axis.
Keywords: adverse drug reactions; antibacterial agents; chronic kidney disease; cognitive impairment; drugs